HIV and new onset seizures: slipping through the cracks in HIV care and treatment. Issue 2 (22nd July 2015) - Sikazwe, I; Elafros, MA; Bositis, CM; Siddiqi, OK; Koralnik, IJ; Kalungwana, L; Theodore, WH; Okulicz, JF; Potchen, MJ; Birbeck, GL
Abstract : Objectives: The aim of the study was to describe patient characteristics and outcomes among HIV‐positive adults presenting to a Zambian tertiary care hospital with new‐onset seizures. Methods: From July 2011 to June 2013, adults with seizures and a known or probable diagnosis of HIV infection were screened for a cohort study. Demographic and clinical data were obtained, including information on engagement in HIV services and in‐patient mortality. Analyses were conducted to identify characteristics associated with poor engagement in care and death. Results: A total of 320 of 351 screened adults were HIV‐positive, with 268 of 320 experiencing new‐onset seizures. Of these, 114 of 268 (42.5%) were female, and their mean age was 36.8 years. Seventy‐nine of the 268 patients (29.5%) were diagnosed with HIV infection during the index illness. Among those who were aware of their HIV‐positive status, 59 of 156 (37.8%) had disengaged from care. Significant functional impairment (Karnofsky score < 50) was evident in 44.0% of patients. Cerebrospinal fluid was not obtained in 108 of 268 (40.3%). In‐patient mortality outcomes were available for 214 patients, and 47 of these 214 (22.0%) died during hospitalization. Patients with significant functional impairment were more likely to undergo lumbar puncture ( P  = 0.046). Women and the functionally impaired were more likely to die ( P  = 0.04 and < 0.001, respectively). Conclusions: Despite the availability of care, less than half of HIV‐infected people with new‐onset seizures were actively engaged in care and in‐patient mortality rates were high. In the absence of clinical contraindication, lumbar puncture should be performed to diagnose treatable conditions and reduce morbidity and mortality. Continued efforts are needed to expand community‐based testing and improve HIV care retention rates. Qualitative studies are needed to elucidate factors contributing to lumbar puncture usage in this population.